Immunotherapy in indolent Non-Hodgkin's Lymphoma. (2022) - Amhaz, Ghid; Bazarbachi, Ali; El-Cheikh, Jean
Abstract: Treatment of non-Hodgkin lymphoma (NHL) in general has improved over the years with the emergence of the monoclonal antibodies (MAB) therapy. NHL is divided into B cell NHL and T cell NHL. Treatment of NHL was based on the subtype of NHL and its staging. NHL is divided into aggressive and indolent NHL (iNHL). Subtypes of iNHL include: Follicular lymphoma (FL), Marginal zone lymphoma (MZL), Chronic lymphocytic leukemia/small-cell lymphocytic lymphoma (CLL/SLL), Gastric mucosa-associated lymphoid tissue (MALT) lymphoma, Lymphoplasmacytic lymphoma, Waldenström macroglobulinemia, Nodal marginal zone lymphoma (NMZL), Splenic marginal zone lymphoma (SMZL). Chemotherapy was the main stay treatment of iNHL until the emergence of Rituximab, anti-CD20 MAB targeting CD-20 surface cell antigens that are present on B-cells lymphoma and not on precursor cells, mainly efficacious in B cell iNHL, It became the mainstay treatment in follicular lymphoma (FL) as a single agent modality or in combination with chemotherapy. The anti-CD20 Rituximab played an important role in the development of the treatment of iNHL to become FDA approved in 1997. It was also proven effective in multiple other types of lymphoma. MAB through targeting the cell surface antigen leads to a direct or immune mediated cytotoxicity. This carries few side effects, including allergic reactions. Other than that, a resistance mechanism to rituximab emerged by inducing a failure in the apoptosis mechanism. Alternative mechanisms of resistance included the presence of soluble antigens that could act by binding to the antibody present before the drug itself can bind the lymphoma cell. Thus, the interest in immunotherapy grew further to explore the possibility of conjugating an immune mediated drug to a radio-sensitizing agent in order to enhance the selectivity of the drug. Here came the development of 90Y-ibritumomab tiuxetan and 131I-tositumomab. After it, humanized anti-CD20 emerged ofatumumab, IMMU106 (veltuzumab) in 2005, and ocrelizumab which are considered as second generation anti-CD20 and 3 rd generation anti-CD20 include AME-133v (ocaratuzumab), PRO131921 and GA101 (obinutuzumab). Also multiple other agents emerged targeting different surface cell antigens like CD52 (alemtuzumab), CD22 (unconjugated epratuzumab and calicheamicin conjugated CMC-544 [inotuzumab ozogamicin]), CD80 (galiximab), CD2 (MEDI-507 [siplizumab]), CD30 (SGN-30 and MDX-060 [iratumumab], Brentuximab vedotin), CD40 (SGN-40), and CD79b (Polatuzumab). Other agents include MAB targeting T-Cells like mogamulizumab, Denileukin Diftitox and BiTEs or bispecific T cell engagers like Mosunetuzumab, Glofitamab, and Epcoritamab. Moreover, further studies came up to evaluate the role of immunotherapy in combination chemotherapy as a pathway to evade the resistance mechanisms. Side effects of the treatment were mainly infusion related adverse reactions, myelosuppression in conjugated forms leading to immunosuppression and subsequently to infectious complications. Another important aspect in immunotherapy is the half-lives of the medication which is an important factor that can influence the evaluation of the response. The MAB treatment showed important benefit in the treatment of iNHL and it continuously shows how rapidly it can develop to provide optimum care and benefit to patients with iNHL.